2017
DOI: 10.1186/s12862-017-1051-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of brain size evolution in cetaceans: insights from adaptive evolution of seven primary microcephaly (MCPH) genes

Abstract: BackgroundCetacean brain size expansion is an enigmatic event in mammalian evolution, yet its genetic basis remains poorly explored. Here, all exons of the seven primary microcephaly (MCPH) genes that play key roles in size regulation during brain development were investigated in representative cetacean lineages.ResultsSequences of MCPH2–7 genes were intact in cetaceans but frameshift mutations and stop codons was identified in MCPH1. Extensive positive selection was identified in four of six intact MCPH genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…31 Odontocete lineages with increased EQ show significant evidence of positive selection; however, absolute brain and body mass do not relate to ASPM selection rates. 31 In addition, ASPM variation is related to neonatal brain size in non-primate clades such as Glires and Euungulata. 32 Studies have also found signatures of positive selection in the hominoid (ie, ape) phylogeny, with higher ratios of non-synonymous to synonymous change found along the lineages leading to the human branch.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…31 Odontocete lineages with increased EQ show significant evidence of positive selection; however, absolute brain and body mass do not relate to ASPM selection rates. 31 In addition, ASPM variation is related to neonatal brain size in non-primate clades such as Glires and Euungulata. 32 Studies have also found signatures of positive selection in the hominoid (ie, ape) phylogeny, with higher ratios of non-synonymous to synonymous change found along the lineages leading to the human branch.…”
mentioning
confidence: 90%
“…[28][29][30][31] For example, acceleration of nonsynonymous substitutions in ASPM is significantly related to encephalization quotient (EQ) in cetaceans, suggesting that the gene may have contributed to relative brain size expansion. [28][29][30][31] For example, acceleration of nonsynonymous substitutions in ASPM is significantly related to encephalization quotient (EQ) in cetaceans, suggesting that the gene may have contributed to relative brain size expansion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations